The Implication of the Helium-to-proton Flux Ratio in Galactic Cosmic Rays - Xiaojian Song; Xi Luo (The Astrophysical Journal, 2023)
The measurement of daily proton and helium fluxes by AMS-02 shows that the helium-to-proton flux ratio (He/H) is negatively correlated with the solar activity at rigidity 1.7–7 GV. What is the behavior of He/H at rigidity lower than 1.7 GV? How can this phenomenon be described quantitatively and linked to the underlying mechanisms? In this work, based on a theoretical derivation, we find that the slope ( S ) of $ln(He/{\rm{H}})$ versus ln(H) is a good indicator of the variation of He/H. S > 0 means the variation of He/H is anticorrelated with the solar activity, and vice versa. Furthermore, the value of S is quantitatively related to the difference in protons and helium nuclei in the local interstellar spectrum (LIS) and in solar modulation. A 3D time-dependent numerical model is used to reproduce the observed proton and helium data. The results of the simulation show that, with increasing rigidity, the parameter S increases from negative values to positive values at around 1 GV, reaches a maximum value at around 2 GV, and then decreases until it approaches 0. Interestingly, S is equal to 0 at around 1 GV. This means that He/H at this rigidity is almost unchanged with the variation in solar activity. Finally, the expression for S is validated by changing the LIS used in the numerical procedure. This shows that the overall profile of S as a function of rigidity is mainly determined by the mass-to-charge ratio, and the specific value of S is strongly affected by the difference in the LIS between protons and helium nuclei.